Luminescent Difluoroboron β-Diketonate PEG-PLA Oxygen Nanosensors for Tumor Imaging - Samonina-Kosicka, Jelena (Macromol Rapid Commun, 2015)
Surface modification of nanoparticles and biosensors is a dynamic, expanding area of research for targeted delivery in vivo. For more efficient delivery, surfaces are PEGylated to impart stealth properties, long circulation and enable enhanced permeability and retention (EPR) in tumor tissues. Previously, BF(2)dbm(I)PLA was proven to be a good oxygen nanosensor material for tumor hypoxia imaging in vivo, though particles were applied directly to the tumor and surrounding region. Further surface modification is needed for this dual-emissive oxygen sensitive material for effective intravenous (IV) administration and passive and active delivery to tumors. In this paper an efficient synthesis of a new dual-emissive material BF(2)dbm(I)PLA-mPEG is presented and in vitro stability studies were conducted. It is found that fabricated nanoparticles are stable for 24 weeks as a suspension, while after 25 weeks the nanoparticles swell and both dye and polymer degradation escalates. Preliminary studies show BF(2)dbm(I)PLA-mPEG nanoparticle accumulation in a window chamber mammary tumor 24 hours after IV injection into mice (C57Bl/6 strain) enabling tumor oxygen imaging.